Carbon partitioning in a wet and a semiwet subarctic mire ecosystem based on in situ C-14 pulse-labelling - Olsrud, Maria; Christensen, Torben (Soil Biology and Biochemistry, 2011)
In this study we quantify the partitioning of recent assimilates to above- and below-ground carbon (C) pools in two subarctic mire ecosystems - wet minerotrophic and semiwet ombrotrophic mire - using in situ C-14 pulse-labelling. Ecosystem C partitioning to rhizomes, coarse roots, fine roots, dissolved organic carbon (DOC) and microbes were quantified twice during the growing season at three different soil depths. Finally the C-14-partitioning data from this and a previous study were combined to estimate the overall C partitioning of the three main vegetation types of a Scandinavian subarctic mire in early and late summer. The semiwet ombrotrophic ecosystem hosted a much larger root biomass on an area basis compared to the wet minerotrophic ecosystem which might be due to differences in the soil nutrient level. Microbial C was found to be the largest C-pool in both ecosystems. Ecosystem C-14 partitioning was poorly related to plant biomass for the semiwet and the wet ecosystem. Overall a higher partitioning of recent assimilates to below-ground compartments was apparent in August-September compared to June-July, while the opposite was found for the above-ground C-pools. In the semiwet ecosystem twice as much C-14 was found in DOC compared to the wet ecosystem, where root density, litter and above-ground biomass were important controls of the C-14-recovery in DOC. Plant-derived DOC was estimated to be 15.4 versus 12.9 mg C m(-2) d(-1) in the semiwet and wet ecosystem, respectively. Graminoid dominated and dwarf shrub dominated vegetation types of the subarctic mire Stordalen differ with respect to the relative amount of recently assimilated C partitioned to C-pools with "slow" versus "fast" decomposition rate. The capacity for sequestration of recently fixed C within "slow" C-pools might affect the ecosystem C balance (NEE) and C-storage. The potential for vegetation changes might therefore be an important factor to consider in studies of response of ecosystem C-dynamics to global change factors in subarctic ...